The effects of type of tooth and the placement site of electrode on the electrical pulp testing of the anterior teeth - Talal H Al-Salman (University of Mosul, College of Dentistry, 2005)
Abstract The aim of this study is to evaluate the effect of type of the tooth and the placement site of electrode on electrical pulp testing of the anterior teeth. Twenty persons were participated in this study. The six maxillary and mandibular anterior teeth were checked to evaluate the response threshold to electrical pulp testing; each tooth was examined at four placement sites on its labial surface, which are the incisal edge, incisal third, middle third and the cervical third. The results showed that the response threshold of the mandibular anterior teeth was lower than that of the maxillary anteriors. The canines may respond to the electrical stimulus in a highest threshold than the lateral incisors and the central incisors which had the lowest response threshold. Also, this study showed that the best placement site of electrode was in the incisal edge of the tooth and the pulp tester reading was increased as the electrode moved toward the cervical region of the tooth.